High-performance liquid chromatography and derivative spectrophotometry for simultaneous determination of pravastatin and fenofibrate in the dosage form - Hefnawy Mohamed M.; Mohamed Mostafa S.; Abounassif Mohammed A.; Alanazi Amer M.; Mostafa Gamal A. E. (Acta Pharmaceutica)
High performance liquid chromatography (HPLC) and second-order derivative spectrophotometry have been used for simultaneous determination of pravastatin (PS) and fenofibrate (FF) in pharmaceutical formulations. HPLC separation was performed on a phenyl HYPERSIL C18 column (125 mm × 4.6 mm i.d., 5 μm particle diameter) in the isocratic mode using a mobile phase acetonitrile/0.1 % diethyl amine (50:50, V/V, pH 4.5) pumped at a flow rate of 1.0 mL min-1. Measurement was made at 240 nm. Both drugs were well resolved on the stationary phase, with retention times of 2.15 and 5.79 min for PS and FF, respectively. Calibration curves were linear (R = 0.999 for PS and 0.996 for FF) in the concentration range of 5-50 and 20-200 µg mL-1 for PS and FF, respectively. Pravastatin and fenofibrate were quantitated in combined preparations also using the second-order derivative response at 237.6 and 295.1 nm for PS and FF, respectively. Calibration curves were linear, with the correlation coefficient R = 0.999 for pravastatin and fenofibrate, in the concentration range of 5-20 and 3-20 µg mL-1 for PS and FF, respectively. Both methods were fully validated and compared, the results confirmed that they were highly suitable for their intended purpose.